2015
DOI: 10.1177/0020715215626238
|View full text |Cite
|
Sign up to set email alerts
|

Cohesion, consensus, and conflict: Technocratic elites and financial crisis in Mexico and Argentina

Abstract: Observers of economic policy-making in developing countries often suggest that consensus and cohesion within technocratic policy elites facilitate the implementation and consolidation of reforms, but have not clearly defined these terms or the relationship between them. Likewise, political sociologists argue that social networks account for elite cohesion, but have not adequately specified the relevant structural properties of these networks. This article argues that structural network cohesion facilitates eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The rhetoric of policy integration thus never fully resonated with reality, even when national planning strategies had broad support and were enacted. Elite competition, which included segments of political, economic, military and sometimes academic elites, transpired in the competition between ministries and their projects (Van Gunten, 2015). It undermined the reality effects of any overarching strategy for spatial development.…”
Section: Discussionmentioning
confidence: 99%
“…The rhetoric of policy integration thus never fully resonated with reality, even when national planning strategies had broad support and were enacted. Elite competition, which included segments of political, economic, military and sometimes academic elites, transpired in the competition between ministries and their projects (Van Gunten, 2015). It undermined the reality effects of any overarching strategy for spatial development.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, however, the extant literature provides significantly fewer cues. Though various features of elite groups and the policy debate, such as the institutional networks connecting elites (Van Gunten 2015), horizontal trust between them (Weinberg 2022), or the role of policy framing when faced with policies that potentially conflict with their interests (Teigen and Karlsen 2020) have been identified as possible determinants of elite support, we lack a coherent account of the origins of elite support behind government policies. Tellingly, in a twowave survey of MEPs' immigration attitudes some time before the refugee crisis, Lahav and Messina (2005) document a convergence of views without specifying the driving mechanisms.…”
Section: The Importance Of Elite Support Behind Government Policiesmentioning
confidence: 99%
“…The acceptance of long-term cost-sharing projects of redistribution requires underlying structures that facilitate agreements and inducement among business elites. Theories and studies on network analysis showed that cohesive networks promote the mobilization of resources for collective action [36], more participation of actors [37], effective transfer of information [38], reduction of uncertainty and transaction costs [39], similar behavior [40], shared beliefs [41], consensus [42], and may even increase the legitimacy of actions. Network cohesion also generates opportunities for social control and peer-inducement, which brings more standardization of preferences, and less autonomy [43,44].…”
Section: Business Cohesion and Redistributive Social Policiesmentioning
confidence: 99%